Chiral squaramide-catalysed one-pot enantioselective sulfa-Michael addition/thioesterification of thiols with α,β-unsaturated N-acylated succinimides - Zhao, Bo-Liang; Du, Da-Ming (Organic & biomolecular chemistry, 2014)
A novel highly enantioselective one-pot dithiolation through sulfa-Michael addition/thioesterification of thiols with alpha,beta-unsaturated N-acylated succinimides catalysed by squaramide has been developed. This organocatalysed reaction proceeded well in high to excellent yields (up to >99%) to afford useful bioactive beta-sulfated thioester derivatives with high enantioselectivities (up to 96% ee).